Introduction to special issue: galectins go with the flow - Rabinovich, Gabriel Adrián (2014)
Galectins, a family of conserved carbohydrate-binding proteins, have recently emerged as regulators of endothelial cell biology and angiogenesis. This series of reviews dissects the individual roles of galectin-1, -3, -8 and -9 in angiogenesis, highlights their regulation by hypoxia and emphasizes the relevance of these endogenous lectins at different stages of tumor metastasis. The human vasculature is the body's infrastructure that facilitates the transport of molecules and cells throughout the body. In addition, blood vessels contribute to proper development and homeostasis of immune responses, coagulation and neovascularization. The cells responsible for these activities are the cells lining the luminal side of all blood vessels, i.e. endothelial cells. Although most studies on angiogenesis have focused on ligand binding …